Watching, Waiting: The Photographic Representation of Empty Places (Prostor, 2024)
Embracing the Covid-19 pandemic as an opportunity for critical reflection, 'Watching, Waiting: The Photographic Representation of Empty Places' explores the landscapes of emptiness through the medium of photography. While the motifs of emptiness are not exclusively tied to the pandemic, its profound impact has offered a new standpoint for reflection. Featuring contributions from diverse authors, the book delves into both contemporary and historical manifestations of emptiness, offering a layered and multidisciplinary reading of the topic.